How do African millionaires spend their money? - Pelizzo, Riccardo (African Politics and Policy Newsletter, 2019)
As we noted in a previous post, Africa has 145000 High Net Worth Individuals whose assets are worth about 800 billion. Overall Africans’ net worth is estimated in 2.2 trillion US dollars. The number of HNWIs has increased considerably in the past decade and is expected to grow nearly as much in the next decade....
Keywords: African politics